QTL analysis of measures of mouse home-cage activity using B6/MSM consomic strains - Nishi, Akinori (Springer-Verlag, 2010)
The activity of mice in their home cage is influenced greatly by the cycle of light and dark. In addition, home-cage activity shows remarkable time-dependent changes that result in a prominent temporal pattern. The wild-derived mouse strain MSM/Ms (MSM) exhibits higher total activity in the home cage than does C57BL/6 (B6), a commonly used laboratory strain. In addition, there is a clear strain difference in the temporal pattern of home-cage activity. This study aimed to clarify the genetic basis of strain differences in the temporal pattern of home-cage activity between MSM and B6. Through the comparison of temporal patterns of home-cage activity between B6 and MSM, the pattern can be classified into five temporal components: (1) resting phase, (2) anticipation phase, (3) 1st phase, (4) 2nd phase, and (5) 3rd phase. To identify quantitative trait loci (QTLs) involved in these temporal components, we used consomic strains established from crosses between B6 and MSM. Five consomic strains, for Chrs 2T (telomere), 3, 4, 13, and 14, showed significantly higher total activity than B6. In contrast, the consomic strains of Chrs 6C (centromere), 7T, 9, 11, and 15 were less active than B6. This indicates that multigenic factors regulate the total activity. Further analysis showed an impact of QTLs on the temporal components of home-cage activity. The present data showed that each temporal component was regulated by different combinations of multigenic factors, with some overlap. These temporal component-related QTLs are important to understand fully the genetic mechanisms that underlie home-cage activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00335-010-9289-z) contains supplementary material, which is available to authorized users.